2002
DOI: 10.1080/09629350220131944
|View full text |Cite
|
Sign up to set email alerts
|

Levels of soluble ICAM‐1 in premature and full‐term neonates with infection

Abstract: BACKGROUND: Infection in the neonatal period is an extremely serious condition and diagnosis is difficult. C-reactive protein (CRP) is widely used as a marker of infection; however, its usefulness is limited in the early phase. The role of soluble intracellular adhesion molecule-1 (sICAM-1), an adhesion molecule, has been examined in recent studies as an early marker of neonatal infection with controversial results. AIM: Assessment of sICAM-1 concentrations and correlation with CRP, which is the currently used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The median pre-transfusion concentration of IL-8 was 35 pg/ml in Group 1 neonates and 65 pg/ml in Group 2 neonates. These concentrations were greater than previously reported concentrations by Lusyati et al 17 However, the reported concentrations in the current study were in line with those of Apostolou et al, 18 who reported a median sICAM-1 level in preterm neonates of 469.6 ng/ml and in full term neonates one of 353.4 ng/ml. They concluded that prematurity resulted in increased serum concentration of sICAM1.…”
Section: Discussionsupporting
confidence: 90%
“…The median pre-transfusion concentration of IL-8 was 35 pg/ml in Group 1 neonates and 65 pg/ml in Group 2 neonates. These concentrations were greater than previously reported concentrations by Lusyati et al 17 However, the reported concentrations in the current study were in line with those of Apostolou et al, 18 who reported a median sICAM-1 level in preterm neonates of 469.6 ng/ml and in full term neonates one of 353.4 ng/ml. They concluded that prematurity resulted in increased serum concentration of sICAM1.…”
Section: Discussionsupporting
confidence: 90%
“…Berner et al and Dollner et al did not find an association between sICAM among septic infants [ 37 , 38 ]. In contrast, studies by Hansen et al, Apostolu et al, and Figueras et al found increased levels of sICAM-1 among septic infants compared with controls [ 40 , 43 , 62 ], and Edgar et al demonstrated that sICAM-1 levels predicted infection in newborns [ 41 , 42 ]. Interestingly even in non-septic newborns, levels of circulating sICAM-1 have been shown to increase over the first week of life; by 30 days of life, plasma concentrations can exceed those of healthy adults [ 63 ].…”
Section: Discussionmentioning
confidence: 94%
“…Research conducted by Routsi et al reports that S100β levels increase in critical patients without brain damage and support the opinion that increased S100β levels may be associated with tissue hypoperfusion. 7 While research by Hsu et al Concluded that an increase in S100β and NSE in serum showed that septic shock caused the release of protein structures originating from brain cells, and this release indicated neurological damage. 8 In this study, the mean value of S100β on the first day of sepsis was 0.085 (0.001 -0.142) ng / mL and the third day was 0.006 (0.001 -0.137) ng / mL.…”
Section: Discussionmentioning
confidence: 99%
“…Serum ICAM-1 values increase first (on the first day) compared to CRP values, so serum ICAM-1 measurements can be useful for early detection of sepsis in neonates suspected of having an infection, so that antibiotic administration can begin immediately and improve outcome. 7 S100β is an astrocyte protein that is responsible for intracellular calcium homeostasis. Several previous studies have shown that brain cell damage is characterized by an increase in serum S100β levels.…”
Section: Introductionmentioning
confidence: 99%